EFFECTIVE CROSS-CULTURAL DIALOGUE: CHALLENGES AND OPPORTUNITIES - Swamp, Tekaronianeken / Jake; Lambe, Jeff (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2002)
ABSTRACT. When one engages in cross-cultural dialogue in situations where vast cultural differences are involved, it comes as no surprise that misunderstandings can arise. This can happen particularly in education initiatives where Native culture is being shared with non-Native people. Contentious issues between Native and non-Native people reflect very different worldviews, an oppressive history and a challenged present. Discussing challenges in cross-cultural dialogue between Native and non-Native people can be a beginning to remedy larger issues of history, race, and culture, benefiting Native/non-Native relationships now and in the future. EFFICACITÉ DU DIALOGUE INTERCULTUREL : DÉFIS ET POSSIBILITÉS RÉSUMÉ. Lorsqu'on amorce un dialogue interculturel là où existent de profondes différences culturelles, il faut s'attendre à des malentendus. Cela se produit particulièrement dans les initiatives d'éducation où la culture autochtone est souvent partagée avec des non-Autochtones. Les questions litigieuses entre les Autochtones et les non-Autochtones reflètent des points de vue différents sur l'univers, des antécédents d'oppression et un présent remis en question. L'analyse des défis dans un dialogue interculturel entre Autochtones et nonAutochtones peut être un premier pas pour remédier à de plus grands problèmes d'histoire, de race et de culture qui seront bénéfiques aux rapports entre Autochtones et non-Autochtones aujourd'hui et demain.